Efficiency and Effectiveness of Defatting with Various Extraction Methods and Solvent Purity - Nugraha Yuwana; Ni Ketut Leseni (Jurnal Teknologi dan Manajemen Pengelolaan Laboratorium, 2022)
Chemical analysis in the laboratory such as crude fiber content, dietary fiber content or starch content generally required defatting which made the analysis more optimal. Some defatting was done by maceration method but there were some methods such as soxhlet (lfat content analysis) and an extraction method using one extractor or single soxhlet. The solvents used for defatting grades also vary, such as pro-analyst and technical. This study used a completely randomized design (CRD) with 3 levels factor for factors A and B, and 2 levels factor of factor C. Factor A was the type of raw material, while factor B and C were defatting method and solvent purity, respectively. The results showed that the use of various defatting methods and differences in solvent purity/grade had a significant effect on sesame seeds, chicken meat, and sausages. The samples fat which extracted the most, were sesame seeds used the single Soxhlet method and pro-analyst benzene solvent. The highest extracted fat of sesame seeds achieved 93% with single Soxhlet method. In general, the most optimal defatting method recommended for continued research or laboratory practice was single soxhlet with pro-analyst or technical solvents.